Integrated Discourse Therapy After Glioblastoma: A Case Report of Face-To-Face and Tele-NeuroRehabilitation Treatment Delivery - Milman, Lisa; Anderson, Emma; Thatcher, Katelyn; Amundson, Deborah; Johnson, Chance; Jones, Morgan; Valles, Louie; Willis, Dale (Frontiers in Neurology, 2020)
BACKGROUND: Language and communication impairments are among the most frequently reported long-term behavioral consequences of brain tumor. Such deficits may persist long after a patient has been discharged from the hospital and can significantly impact return to work, resumption of prior social roles and interpersonal relations, as well as full engagement in leisure activities. While considerable research has centered on identifying and describing communication impairments in brain tumor survivors, relatively little research has investigated language therapy for this population. AIMS: This report 1) reviews the literature and describes the language and cognitive-communicative profile of a 35-year-old man six years post glioblastoma excision with subsequent chemo- and radiation therapies; 2) presents cognitive-communication outcome data for this individual following an integrated discourse therapy; and 3) assesses treatment feasibility in face-to-face (F2F) and tele-neurorehabilitation (TNR) contexts. METHODS: A battery of tests and weekly conversation probes were administered to evaluate baseline performance and potential changes associated with F2F and TNR treatment delivery. Integrated Conversation Therapy (ICT) was administered across four alternating (F2F and TNR) treatment blocks over two months. ICT is a solution-focused discourse intervention that simultaneously targets word finding, sentence processing, and authentic patient-selected conversational interactions. RESULTS: Although the participant presented with long term-language impairments that were clinically distinct from stroke-associated aphasia, statistically significant post-treatment gains ( > 2 SEM) were evident following F2F and TNR treatment delivery on standardized measures of apraxia, discourse production, verbal memory, and self-ratings of discourse production, communication, and living with aphasia. While objective measures of treatment effect size (probes of CIU discourse data) were consistent across F2F and TNR delivery models, results of a satisfaction survey indicated a slight but statistically significant participant preference for TNR treatment delivery. CONCLUSIONS: This study provides preliminary support for F2F and TNR delivery of ICT discourse intervention for glioblastoma survivors. It also highlights the need for more research specifically dedicated to language therapy for this population.